2018
DOI: 10.1111/ggi.13516
|View full text |Cite
|
Sign up to set email alerts
|

Community‐dwelling older men with dementia are at high risk of hip fracture, but not any other fracture: The Concord Health and Aging in Men Project

Abstract: Older men with dementia, but not MCI, have a greater tendency to fall and sustain hip fractures, but not any other types of fractures. Geriatr Gerontol Int 2018; 18: 1479-1484.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…This finding is also consistent with our results that the osteoporosis group had a 1.27-fold higher risk of AD (95% CI = 1.22–1.32) than the matched control group (incidence rates: 10.4 and 6.8 per 1,000 person-years, respectively). However, some studies have reported results contradicting the association between AD or dementia and osteoporosis (Guo et al, 2012 ; Hsu et al, 2018 ), but these studies did not include a general population without osteoporosis as a control and had selection bias, as they evaluated either only older men aged 70–94 years or psychiatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is also consistent with our results that the osteoporosis group had a 1.27-fold higher risk of AD (95% CI = 1.22–1.32) than the matched control group (incidence rates: 10.4 and 6.8 per 1,000 person-years, respectively). However, some studies have reported results contradicting the association between AD or dementia and osteoporosis (Guo et al, 2012 ; Hsu et al, 2018 ), but these studies did not include a general population without osteoporosis as a control and had selection bias, as they evaluated either only older men aged 70–94 years or psychiatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in some studies, comorbidities are noted to be associated with falls, and in others, there is no association (Galik, Holmes, & Resnick, 2018;Urrunaga-Pastor et al, 2018). Cognitive status tends to be associated with falls such that those who are impaired, particularly those with mild impairment, are more likely to sustain a fall (Hsu et al, 2018). In the current study, we used the single three out of three word recall item from the Mini-Cog to describe cognitive status, and this may not have been sensitive enough to differentiate those with mild, moderate, or severe impairment.…”
Section: Discussionmentioning
confidence: 99%
“…32,33,[35][36][37][38][39][40][41][42][43][44][45][46] The mean age of participants with Mild Cognitive Impairment was 75.1 years (standard deviation 5.9). Females ranged from 0% 34 to 100% 47 of the sample, with the average being 59% (standard deviation 18.4).…”
Section: Study Characteristicsmentioning
confidence: 99%